Typing Candida albicans oral isolates from healthy Brazilian schoolchildren using multilocus enzyme electrophoresis reveals two highly polymorphic taxa - Boriollo, Marcelo Fabiano Gomes; Spolidório, Denise Madalena Palomari [UNESP]; Barros, Letizia Monteiro; Bassi, Rodrigo Carlos; Garcia, José Antonio Dias; Costa, Ana Maria Duarte Dias; Rosa, Edvaldo Antonio Ribeiro; Höfling, José Francisco (Sociedade Brasileira de Microbiologia, 2011)
The genetic diversity of C. albicans oral isolates from 75 healthy schoolchildren from eight schools located in different geographic areas of Piracicaba city, São Paulo state, Brazil, was established using isoenzymes marker (Multilocus Enzyme Electrophoresis - MLEE) and cluster analysis. Patterns of monoclonal and polyclonal oral colonization by C. albicans within and between groups of schoolchildren were identified. However, significant divergence between the observed and the expected genotypic frequencies (Hardy-Weinberg equilibrium test) was not detected in the geographically adjacent groups, suggesting the hypothesis that populations of healthy schoolchildren do not correspond to the selection factor (differential survival) of strains. Two highly polymorphic and distantly genetically related taxa (A and B) were identified within the total population of yeasts, each contained subgroups (A1, A2, A3, A4, B1 and B2) and clusters of moderately related strains (from I to X), suggesting the existence of strains restricted or not to certain groups of geographically limited, healthy students. However, the coexistence of identical strains in healthy schoolchildren from the same school (geographically related) reinforces the hypothesis of oral transmission, where the sources of propagation could be explored. Furthermore, this could also be used in current and retrospective analyses of C. albicans isolated from immunocompetent and immunocompromised people, in order to detect commensal or potentially pathogenic yeast groups, predominantly in candidiasis, and in the development of strategies to prevent transmission or human propagation.
Keywords: Candida albicans; healthy schoolchildren; geographic region; MLEE; cluster analysis